L’art entre hubris et mania. Du pathologique au sublime (Lebenswelt. Aesthetics and philosophy of experience., 2023)
From Empédocle to Paul Celan, there have always been poets, artists whose works lead to the surpassing of the limits of meaning. They rub shoulders with absolute reality and get lost in it. On the other hand, there are those so-called "mad" mental patients who, in their insanity and delirium, desperately try to expel the symptom that strikes them. If, for the former, their works are based on inconsistencies that bring them to the extreme limit of tearing, for the latter, it is on the contrary a matter of sealing the tear that is tearing them apart.